2006
DOI: 10.1158/0008-5472.can-05-2354
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Signaling Pathways Involved in the Cell Growth Inhibition of Glioma Cells by Melatonin

Abstract: Melatonin is an indolamine mostly produced in the pineal gland, soluble in water, and highly lipophilic, which allows it to readily cross the blood-brain barrier. Melatonin possesses antioxidant properties and its long-term administration in rodents has not been found to cause noteworthy side effects. In the present work, we found that millimolar concentrations of this indolamine reduced cell growth of C6 glioma cells by 70% after 72 hours of treatment, inhibiting cell progression from G 1 to S phase of the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
137
3
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(153 citation statements)
references
References 45 publications
12
137
3
1
Order By: Relevance
“…Neurological disorders which have been reported to be improved by administration of melatonin are as follows: Parkinsonism [10], Alzheimer's disease [11], brain edema and traumatic brain injury [12], alcoholism [13], depression [14], cerebral ischemia [15], hyperhomocysteinuria [16], glioma [17] and phenylketonuria [18]. Alzheimer's disease is an age-related progressive neurodegenerative disorder, characterized with loss of cognitive functions, dementia and other neurobiological findings [2,19].…”
Section: öZmentioning
confidence: 99%
“…Neurological disorders which have been reported to be improved by administration of melatonin are as follows: Parkinsonism [10], Alzheimer's disease [11], brain edema and traumatic brain injury [12], alcoholism [13], depression [14], cerebral ischemia [15], hyperhomocysteinuria [16], glioma [17] and phenylketonuria [18]. Alzheimer's disease is an age-related progressive neurodegenerative disorder, characterized with loss of cognitive functions, dementia and other neurobiological findings [2,19].…”
Section: öZmentioning
confidence: 99%
“…Melatonin has been shown to have neuroprotective effects in a large number of different experimental models (Cos et al, 1996;Armstrong and Niles, 2002;Feng and Zhang, 2004;Rincón Castro et al, 2005;Martín et al, 2006;Herrera et al, 2007). However, there is limited evidence suggesting that melatonin may affect glioblastoma growth.…”
mentioning
confidence: 99%
“…It has been also reported that melatonin at millimolar concentrations reduces, both in vitro and in vivo, the growth of C6 glioma cells (26,30). This inhibition has been related to reduced intracellular peroxides and a subsequent inhibition of the activity of important intracellular effectors, such as Akt and nuclear factor (NF)-κB and protein kinase C (26,30). In addition to the beneficial effects of providing direct antioxidant protection to glioma cells, melatonin may enhance neuroprotection against Aß-induced neurotoxicity by attenuating Aß25-35 or Aß1-42-induced apoptosis and promoting the survival of glial cells (24).…”
Section: Introductionmentioning
confidence: 95%
“…Melatonin has been shown to have neuroprotective effects in a large number of different experimental models (22)(23)(24)(25)(26)(27) and there is evidence suggesting that melatonin may affect glioblastoma growth. In a clinical trial in which melatonin was administered to patients being treated with radiation therapy for glioblastoma, a significant increase in one-year survival was seen (28).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation